Bid - Ask, Volume, Price Sebelum dan Sesudah Multiple Listing - Abigail Tandi Padang (Fakultas Bisnis UKDW, 2008)
Multiple Listing is generatly fup by d compery when tlw orrount of the find necded by tre aryoty wouW rct befutfilld by tte local stocb alone This resewch oilnd d Wing the diffqqce betnes, bieqsk, wfume, md price before od der the compmy *ecutd mitiple l*W in 2ftr/0 n 20M. 7'te twotlresis was oufued W qrptqfurg stqtiIiql wbsis of non-prormric of Wilcuon Tlp quAsis rqult qlqid thd tlwe were ffisenees of bi&ask sprpnd whnne, od price before and fi.er a,Mtlng ,rnitipii listing.Kaywords: Muttiple listing, bid–ask spread, volume, and price.